Seksisme sebagai moderator hubungan sense of community dan kinerja mahasiswa organisatoris - Andi Hakiki; Muhammad Fath Mashuri (Fakultas Psikologi, 2021)
The performance of student organizations is a crucial variable in maintaining their existence and achieving their organizational goals. One of the important factors that influence this is the degree of sense of community of the members of the organization. Sexism as a gender prejudice is considered to have the potential to influence aspects of the sense of community and organizational performance. This study aims to examine sexism as a moderator on the relationship between sense of community and organizational performance. This study uses a quantitative method and determines the subject using a random sampling technique to the members of student organizations with a total of 223 subjects. The measuring instrument used is Sense of Community version 2, The Ambivalent of Sexism Inventory, and an Organizational Performance Scale. Data analysis used the method of moderated regression analysis. The results showed that there was a significant relationship between sense of community and organizational performance, and sexism as a moderator variable had an insignificant value on the relationship between sense of community and organizational performance. Keywords: Organizational performance, sense of community, sexism, university student